Pierwiastki towarzyszące w fazach szlamów powstających w procesie szybowym pirometalurgicznego otrzymywania cynku i ołowiu = Accompanying elements in phases of sludges formed during shaft furnace pyrometallurgical process of zinc and lead production - Adamczyk, Zdzisław; Nowińska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Zinc Plant "Miasteczko Śląskie" produces zinc and lead by using pyrometallurgical method Imperial Smelting Process (ISP). Technological line of the plant consists of two main units: sinter plant and shaft furnace. Many wastes (sludges, drosses, slags) are producedduring ISP process.
Keywords: odpady; szlamy; pirometalurgia; cynk; ołów; pierwiastki towarzyszące; fazy; wastes; sludge; pyrometallurgy; zinc; lead; accompanying elements; phases